Clinical Correlates and Prognostic Significance of Change in Standardized Left Ventricular Mass in a Community‐Based Cohort of African Americans. Issue 2 (5th February 2015) - Fox, Ervin R.; Musani, Solomon K.; Samdarshi, Tandaw E.; Taylor, Jared K.; Beard, Walter L.; Sarpong, Daniel F.; Xanthakis, Vanessa; McClendon, Eric E.; Liebson, Philip R.; Skelton, Thomas N.; Butler, Kenneth R.; Mosley, Thomas H.; et al.
Abstract : Background: Though left ventricular mass (LVM) predicts cardiovascular events (CVD) and mortality in African Americans, limited data exists on factors contributing to change in LVM and its prognostic significance. We hypothesized that baseline blood pressure (BP) and body mass index (BMI) and change in these variables over time are associated with longitudinal increases in LVM and that such increase is associated with greater incidence of CVD. Methods and Results: We investigated the clinical correlates of change in standardized logarithmically transformed‐LVM indexed to height2.7 (log‐LVMI) and its association with incident CVD in 606 African Americans (mean age 58±6 years, 66% women) who attended serial examinations 8 years apart. Log‐LVMI and clinical covariates were standardized within sex to obtain z scores for both visits. Standardized log‐LVMI was modeled using linear regression (correlates of change in standardized log‐LVMI) and Cox proportional hazards regression (incidence of CVD [defined as coronary heart disease, stroke, heart failure and intermittent claudication]). Baseline clinical correlates (standardized log‐LVM, BMI, systolic BP) and change in systolic BP over time were significantly associated with 8‐year change in standardized log‐LVMI. In prospective analysis, change in standardized LVM was significantly (P=0.0011) associated with incident CVD (hazards ratio per unit standard deviation change log‐LVMI 1.51, 95% CI 1.18 to 1.93). Conclusions: In our community‐based sample of African Americans, baseline BMI and BP, and change in BP on follow‐up were key determinants of increase in standardized log‐LVMI, which in turn carried an adverse prognosis, underscoring the need for greater control of BP and weight in this group.